Global Standards, Corporate Diagrams and Indigenous Agency: ExxonMobil in Russia and Alaska - Tysiachniouk, Maria; Henry, Laura; Horowitz, Leah (Arctic Review on Law and Politics, 2022)
This paper examines how a transnational corporation (TNC) translates global standards and corporate policies into programs at sites of extraction. We explore this question through a comparative analysis of ExxonMobil’s operations in two different politico-economic contexts: the Sakhalin-1 project in Russia and the Point Thomson project on the North Slope of Alaska, with field work on Sakhalin Island in 2013–2015 and in Alaska in 2015–2018. Theoretically, we use the Deleuzian concept of “diagram” as a lens through which to examine corporate policies, and a governance generating network (GGN) approach to analyze similarities and differences in benefit-sharing programs in both localities. We show that while global commitments and corporate principles contribute to a standardized approach to community engagement, Indigenous movements and associations, the government, and other corporate actors may play important roles in influencing how corporate policies and global standards are implemented at sites of extraction. Moreover, adaptation of community engagement, benefit-sharing, and environmental monitoring in one location may shape how the company’s strategies are implemented in other sites of extraction.